PERBAIKAN INTENSITAS CAHAYA MEMPERCEPAT WAKTU REAKSI PADA SISWA KELAS ENAM SEKOLAH DASAR NOMOR 8 DAUH PURI DENPASAR - Bhargah, Agha; Muliarta, Made (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 2 No 1 (2016): Volume 2 No 1 Juni 2016, 2016)
The learning process in a room with low intensity may cause the eyestrain amongstudents, it would be a disadvantage because it makes students become tired and sleepy. The assessment of fatigue used psychomotor reaction time test. This test provides a description of the fatigue that occurs among students. This study aims to investigate the influence of improvement of light intensity to the reaction time among sixth grade students at ElementarySchool Dauh Puri Number 8 Denpasar.This research was using pre experimental study with the one group pre test-post test design among sixth grade students at Elementary School Dauh Puri Number 8 Denpasar. This study used 22 subjects, 11 men and 11 women. The study was conducted first by measuring the reaction time after the first period of study is completed, and then the light intensity improved to meet the standards for one week. The second measurement of the reaction timedid after one week period of the intervention.The results showed a significant difference between the reaction time before the intervention (522 ms) and after the intervention (476 ms), CI 95% : 42.68 – 50.68, p = 0.000. There was additional data regarding the reaction time comparisons between men and women. The reaction time is faster in men (480 ms) than in women (564 ms), p = 0.004. It was concluded that the improvement of light intensity is able to accelerate the reaction time, and reaction time is faster in men than women.
Keywords: reaction time, intensity of light, eye fatigue.